2022
DOI: 10.1038/s41598-022-16821-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of enzymatic hydrolysis by alcalase and flavourzyme to enhance the antioxidant properties of jasmine rice bran protein hydrolysate

Abstract: This study aimed to optimize the hydrolysis conditions for producing jasmine rice bran protein hydrolysate (JBH) using response surface methodology (RSM). The independent variables were the ratio of flavourzyme to alcalase (Fl:Al; 0: 100 to 15: 85; 2.84% enzyme concentration) and hydrolysis time (60–540 min). The optimum hydrolysate was obtained at an Fl:Al ratio of 9.81: 90.19 for 60 min, since it enabled high amounts of protein, high antioxidant activity and more low molecular weight proteins. The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…This pattern indicated that increased hydrolysate yields generally correlated with higher protein content in the hydrolysate. Notably, the outcomes of enzymatic trials surpassed those of the control group, aligning with documented yields for various protein hydrolysates in existing literature (Hall et al 2017 ; Hunsakul et al 2022 ). Moreover, a positive correlation emerged between the degree of hydrolysis and protein content, consistent with findings reported for other protein hydrolysates (Watchararuji et al 2008 ).…”
Section: Resultssupporting
confidence: 71%
“…This pattern indicated that increased hydrolysate yields generally correlated with higher protein content in the hydrolysate. Notably, the outcomes of enzymatic trials surpassed those of the control group, aligning with documented yields for various protein hydrolysates in existing literature (Hall et al 2017 ; Hunsakul et al 2022 ). Moreover, a positive correlation emerged between the degree of hydrolysis and protein content, consistent with findings reported for other protein hydrolysates (Watchararuji et al 2008 ).…”
Section: Resultssupporting
confidence: 71%
“…Under our experimental conditions, the faster Alcalase hydrolysis of chia proteins was achieved at 50 • C incubation [16,25]. This observation aligns with the optimal temperature range for Alcalase activity, which typically falls between 50 and 65 • C [26].…”
Section: Enzymatic Hydrolysis Of Chia Expeller Using Alcalasesupporting
confidence: 84%
“…Zhang et al studied the effect of microfluidization on the functional properties of rice dreg protein before hydrolysis by Alcalase and Neutrase, but the authors did not provide details on the changes in the DH. A combined enzyme hydrolysis of proteins may result in a synergistic effect on both the DH and the biological activities of the hydrolysates. Nevertheless, research on this promising strategy is still very limited and needs to be further explored. Alcalase and Neutrase are bacterial endoproteases produced by Bacillus licheniformis and Bacillus amyloliquefaciens, respectively.…”
Section: Resultsmentioning
confidence: 99%